The villainess turns the hourglass. 8 - SANSOBEE (Comics author) (Ize Press, 2025)
"Princess Bliss Franz believes that she never should've been born and that she is solely to blame for her mother Aria's frailty. So naturally, the best course of action would be to stop her parents from having her at all-a feat that is only possible for a child of Aria and Asher, possessing the ability to travel through both time and space! Keeping her real identity a secret is hard enough, but with an imposing lady-in-waiting watching her every move, potential space-time paradoxes, and a meddlesome twin sister trying to stop her, it's just one obstacle after another! Can Bliss succeed in giving her parents the happy future of her dreams?"--Back cover.